“Se habla español: A Certain Tendency in the Western Film” - Tarancón, Juan A. (Miscelánea: A Journal of English and American Studies, 2007)
If, at any moment, the traditional Turnerian West thesis wavered in its assertion of the significance of the epic frontier narrative in U.S. history, the texts that followed, Hollywood’s films among them, helped solidify and perpetuate a set of values and certainties about gender, race, and land that became a synonym for United States national identity and purpose. Drawing upon these general widespread assumptions, this article examines the role and the impact of frontier narratives in the Hollywood western film. Hollywood films have not always endorsed the official version of history and they often retaliate by challenging in multiple ways the homogeneous mythical view of the frontier experience regarded as dominant and genuine. The writer argues that a number of 1950s films such as The Ride Back! (Allen H. Miner, 1957), The Bravados (Henry King, 1958) or Man from Del Rio (Harry Horner, 1956), focus on the alienation of the traditional hero and on the social tensions in the borderlands of South Texas and portray the West both as the site where the genuine U.S.-ness is to be found and, at the same time, as an empty signifier where the struggle for meaning is played out in the encounter with the other. In addition, this article explores a contemporary border narrative such as Lone Star (John Sayles, 1996) to illustrate how genre films find the mechanisms to call into question the channels that validate and sanction some discourses to the detriment of others.
Keywords: Film studies; Film genre; The West; Identity; U.S. society; Mexico/U.S. border; Chicana/o studies; John Sayles